Template-directed synthesis of Co2P/MoSe2 in a N-doped carbon hollow structure for efficient and stable sodium/potassium ion storage. (March 2022) - Wang, Yuyu; Kang, Wenpei; Pu, Xiangjun; Liang, Yucang; Xu, Ben; Lu, Xiaoqing; Sun, Daofeng; Cao, Yuliang
Abstract: Multi-component hollow structures with attractive physicochemical properties, often show superior electrochemical performance in alkali-ion batteries. Herein, a template-directed strategy is proposed for synthesis of multi-component hollow nanosphere with Co2 P/MoSe2 confined in N-doped carbon (Co2 P/MoSe2 @NC). This structure markedly improves the kinetics, provides sufficient active sites and accommodates volume expansion, for the large-sized K + /Na + storage, which is proved by the in-situ and ex-situ transmission electron microscopy measurements. As for sodium storage, a capacity of 230 mAh g −1 over 1500 cycles can be retained at current of 2.0 A g −1, with a capacity retention of 83%. In terms of K + storage, Co2 P/MoSe2 @NC anodes display excellent rate capability and ultra-long cycling performance (177.6 mAh g −1 at 1.0 A g −1 for 5000 cycles with a capacity retention of 75%). Based on the analysis of electrode process by comparison of d Q /d V curves and theoretical calculations, the intercalation-conversion reaction for K + storage is more reversible and the weaker adsorption of K + on the Co2 P/MoSe2 interface can guarantee the stable storage of the K + -ions. High energy density of 43.34 Wh kg −1 at power densities of 22263.7 W kg −1 is delivered in the Co2 P/MoSe2 @NC//AC potassium-ion hybrid supercapacitor. This indicates that a selenide/phosphide combination can exert useful synergistic effects on the large-sized K + /Na + storage, and is a promising anode candidate. Graphical Abstract: ga1 Highlights: A template-directed strategy was used to construct multi-component hollow structures. Co2 P/MoSe2 confined in NC framework was designed in one-step selenization process. The hollow nanosphere with Co2 P and MoSe2 promotes the high-rate storage of Na + /K + . K + storage is stable for Co2 P/MoSe2 @NC based on d Q/ d V analysis and DFT calculation.